Energy efficient dominating set based topology maintenance in ad hoc wireless networks - Shaikh, Jamil (University of Ottawa (Canada), 2004)
In a multi-hop wireless network, each node is able to send a message to all of its neighbors that are located within its transmission radius. In a broadcasting task, a source sends the same message to the entire network. The routing problem deals with finding a route between a source and a destination. In the activity-scheduling problem, each node decides between active or passive state. We present a scheme whose goal is to prolong network life while preserving connectivity. Each node is either active or has an active neighbor node. Routing and broadcasting are restricted to active nodes that create such dominating set. Activity status is periodically updated during a short transition period. The main contribution of this thesis is to propose new metrics for previously studied source independent localized dominating sets, based on combinations of node degrees and remaining energy levels, for deciding activity status. Furthermore, our implementation of new metrics enhanced the life span of each node and whole network for 12% to 29%. We argue that our new approach can outperform conventional 802.11, conventional dominating set based ad hoc networks and span in terms of capacity, latency, and power savings.
Keywords: Computer Science.